Disinflation and the Supply Side - Agenor, Pierre-Richard; Lodovico, Pizzati (World Bank, Washington, DC, 2014)
The authors study the dynamics of output, consumption, and real wages induced by a disinflation program based on permanent and temporary reductions in the nominal devaluation rate. They use an intertemporal optimizing model of a small open economy in which domestic households face imperfect world capital markets, the labor supply is endogenous, and wages are flexible. The model predicts that, with a constant capital stock and no investment, there is an initial reduction in real wages and output expands. Consumption falls on impact but increases afterward. In addition, with a temporary shock, a current account deficit emerges and, later a recession sets in, as documented in various studies. With endogenous capital accumulation, numerical simulations show that the model can also predict a boom in investment.